Extracellular Degradation Into Adenosine and the Activities of Adenosine Kinase and AMPK Mediate Extracellular NAD+-Produced Increases in the Adenylate Pool of BV2 Microglia Under Basal Conditions - Zhang, Jie; Wang, Caixia; Shi, Haibo; Wu, Danhong; Ying, Weihai (Frontiers in Cellular Neuroscience, 2018)
Cumulating evidence has indicated NAD+ deficiency as a common central pathological factor of multiple diseases and aging. NAD+ supplement is highly protective in various disease and aging models, while two key questions have remained unanswered: 1) Does extracellular NAD+ also produce its effects through its degradation product adenosine? 2) Does extracellular NAD+ produce the protective effects by affecting cells under pathological insults only, or by affecting both normal cell and the cells under pathological insults? Since extracellular NAD+ can be degraded into adenosine, and endogenous adenosine levels are in the nanomolar range under physiological conditions, extracellular NAD+ may produce its effects through its degradation into adenosine. In this study we used BV2 microglia as a cellular model to test our hypothesis that NAD+ treatment can increase the intracellular adenylate pool under basal conditions through its extracellular degradation into adenosine. Our study has shown that extracellular NAD+ is degraded into adenosine extracellularly, which enters BV2 microglia through equilibrative nucleoside transporters under basal conditions. The intracellular adenosine is converted to AMP by adenosine kinase, which increases the intracellular ATP levels by both activating AMPK and increasing the intracellular adenylate pool. Collectively, our study has suggested a novel mechanism underlying the protective effects of NAD+ administration, which is mediated by extracellular NAD+ degradation into adenosine as well as the activities of adenosine kinase and AMPK. Our findings have also suggested that NAD+ administration in various disease and aging models may also produce its effects by affecting the microglia that are not under pathological insults.